ANALISIS PARTISIPASI ANGGOTA KOPERASI TERHADAP PENINGKATAN PENDAPATAN SHU KOPERASI PADA KPN PADANJAKAYA KECAMATAN MARAWOLA TAHUN BUKU 2002-2012 - Rozali, Rozali (Katalogis, 2016)
This study aims to determine the effect of the members participation on the cooperative net income, identify the rapid growth in cooperative net income and determine the contribution of their business unit for savings and loans on the net income of KPN Padanjakaya in Marawola District for fiscal year 2002-2012. This research is categorised as quantitative research through applying descriptive and quantitative analysis method at the same time. This study was conducted to examine the relationship between the participation of the cooperative members on net income. This study was conducted in Marawola district with the object of research is the Civil Servants Cooperative Padanjakaya. This study was conducted in the year 2014 by analysing the cooperative net income for fiscal year 2002-2012. There are several method of analysis in this study include: 1) simple linear regression; 2) analysis of growth, and; 3) analysis of contributions. The results of this study concluded that: 1) The statistical tests results show that the p value sig.2-tailed)> 0.05 so that the Ha hypothesis is accepted with 95% confidence level. This mean that there is a statistically significant in the relationship between the variables of members participation and the cooperative net income. 2) The development of the rapid growth of cooperative net income in the period 2002-2012 have increased on average from year to year but the development have also decreased for certain years in period of survey . The higher members participation, the more higher benefits will be received by cooperative members. 3) The contribution of savings and loan services to the cooperative net income in the period 2002-2012 have increased on average but the contribution have also decreased for certain years in the period of study. The utilisation of credit services (savings and loans) will impact on the cooperative revenue / income, where most of the revenue was used to optimising the working capital for funding daily operations of cooperative.